Monitoring of physical activity levels of guide dog owners – a preliminary study - Laranjo, Luis (2020)
Despite the well-documented benefits of regular physical activity, people with disabilities are often challenged with too many barriers that discourage an active lifestyle. This is particularly evident among people with visual impairments (VI). Previous studies have shown that adults with VI are significantly less active than the general population, and do not meet the physical activity recommendations of the World Health Organisation (WHO). However, most study samples are based on participants using a white cane. Owning a guide dog is often described as a factor for increased mobility and has the potential to increase physical activity. Therefore, the purpose of this preliminary study was to objectively assess the physical activity of adults with VI assisted by a guide dog.